2011
DOI: 10.1203/pdr.0b013e3182181b2c
|View full text |Cite
|
Sign up to set email alerts
|

Total and Acylated Ghrelin Levels in Children With Poor Growth

Abstract: Ghrelin, an enteric hormone with potent appetite stimulating effects, also stimulates growth hormone release. We hypothesized that altered levels of total ghrelin (TG) or acylated ghrelin (AG) could affect growth by altering growth hormone secretion, subsequently affecting insulin-like growth factor-1 (IGF-1) generation or by altering appetite and food intake. After institutional review board approval, 52 children presenting for evaluation of chronic gastrointestinal symptoms (group 1), poor weight gain (group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(29 reference statements)
2
7
0
Order By: Relevance
“…While no children whose height was under percentile 10 were present in H. pylori (-) group in our study, the fact that there were 10 Endogenous ghrelin was shown to stimulate GH secretion from the pituitary gland by activating its receptor (23). Ghrelin may not only play a part in triggering GH release, but could also contribute to positive energy balance by increasing appetite, and these effects, together or separately, could affect growth and weight gain (10). However, the data related to the association between H. pylori infection and plasma level of ghrelin are controversial.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…While no children whose height was under percentile 10 were present in H. pylori (-) group in our study, the fact that there were 10 Endogenous ghrelin was shown to stimulate GH secretion from the pituitary gland by activating its receptor (23). Ghrelin may not only play a part in triggering GH release, but could also contribute to positive energy balance by increasing appetite, and these effects, together or separately, could affect growth and weight gain (10). However, the data related to the association between H. pylori infection and plasma level of ghrelin are controversial.…”
Section: Discussionmentioning
confidence: 60%
“…H. pylori infection is associated with growth failure and possibly lower ghrelin levels (10). On the other hand, the likelihood of the association between H. pylori and growth failure still remains controversial (11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 In addition, no difference in ghrelin levels has been noted between normal and GH-deficient individuals. [27][28][29] Interestingly, AG levels were higher in children with poor weight gain than in those with short stature or chronic gastrointestinal dysfunctions, 30 indicating that AG would be released in response to an energy deficit rather than being submit your manuscript | www.dovepress.com influenced by growth defects per se. Consequently, this either suggests that ghrelin is not essential for the regulation of normal growth functions or that other factors could compensate for its deficient secretion.…”
Section: Biological Activities Of Ghrelin Ghrelin and Gh Secretionmentioning
confidence: 99%